The limits of communication among students of the psychological counseling and educational guidance departments (Journal of the College of Basic Education, 2022)
The current research aimed to identify:1- Limits of communication among students of psychological counseling and educational guidance departments.2- Significance of differences in the limits of communication according to the variable of sex (males, females) among students of the departments of psychological counseling and educational guidance.For the purpose of achieving the objectives of the current research, the researcher: Building the Communication Limits Scale, which consists of (24) items according to the Paulster and Paulster theory. The statistical analysis procedures for the scale were verified by applying it to a sample of (400) students, and the significance of distinction For the items of the scale, as well as the internal consistency and all psychometric properties (apparent validity and construction validity) the scale was applied in its final form on a randomly selected sample of (260) male and female students, and after applying the research tool and using the appropriate statistical methods, the following results were reached:The individuals of the research sample have communication limits according to the difference between the arithmetic mean and the hypothetical meanThere are differences in the relationship of statistical significance to the limits of communication according to the gender variable and in favor of males.